International Civil Law In The Settlement Of Cross-Border Civil Disputes - Ahmad Al Farisi; Muhammad Aziz Zulkifli (PT. Hafasy Dwi Nawasena, 2026)
Globalization has encouraged the increasing development of legal relationships between individuals and legal entities originating from different countries. These interactions have given rise to civil legal relations that are no longer confined to the territory of a single state but involve foreign elements connecting more than one national legal system. This condition has led to a growing number of cross-border civil disputes that require dispute resolution mechanisms capable of ensuring legal certainty, justice, and benefits for the parties involved. In this context, Private International Law (PIL) plays an important role in determining the applicable law (choice of law), the jurisdiction of competent courts, and the recognition and enforcement of foreign judgments. This study aims to analyze the application of Private International Law principles in the settlement of cross-border civil disputes and to identify various challenges encountered in practice. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that the principles of Private International Law serve as essential instruments for resolving legal conflicts arising from the existence of foreign elements in legal relationships. However, their implementation continues to face several obstacles, including jurisdictional conflicts, differences among national legal systems, the lack of uniform rules regarding the recognition and enforcement of foreign judgments, and the national interests of individual states. Therefore, legal harmonization and enhanced international cooperation are necessary to establish a more effective, fair, and legally certain system for resolving cross-border civil disputes.